Adamantane-containing drug delivery systems - Stela Dragomanova; Velichka Andonova (Pharmacia, 2023)
Adamantane is a weakly functional hydrocarbon widely used to develop new drug molecules to improve their pharmacokinetic and pharmacodynamic parameters. The compound has an affinity for the lipid bilayer of liposomes, enabling its application in targeted drug delivery and surface recognition of target structures. This review presents the available data on developed liposomes, cyclodextrin complexes, and adamantane-based dendrimers. Adamantane has been used in two ways – as a building block to which various functional groups are covalently attached (adamantane-based dendrimers) or as a part of self-aggregating supramolecular systems, where it is incorporated based on its lipophilicity (liposomes) and strong interaction with the host molecule (cyclodextrins). Adamantane represents a suitable structural basis for the development of drug delivery systems. The study of adamantane derivatives is a current topic in designing safe and selective drug delivery systems and molecular carriers.